PENGARUH JUMLAH PENDUDUK, UPAH MINIMUM, PERTUMBUHAN EKONOMI DAN TINGKAT PENDIDIKAN TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KABUPATEN GRESIK - Okky Tegar Adinda, Eryan; Asmara, Kiky (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Gresik Regency is a city/district located in East Java Province which has a fairly dense level of economic activity. However, the high level of open unemployment is one of the factors that is hampering economic development in the Gresik Regency area. This research aims to determine the influence of population, minimum wage, economic growth and education level on the level of open unemployment in Gresik Regency. The data used is secondary data obtained from the relevant agency, namely the central statistical agency, over a period of 12 years, namely 2011 to 2022. The analytical method used in this research is multiple linear regression analysis. The results of this research show that the Minimum Wage has an effect, Economic Growth has a negative effect, and the level of education has a partially positive effect and has a partially significant effect on the level of open unemployment in Gresik Regency. Meanwhile, partial population size does not have a significant influence on the level of open unemployment in Gresik Regency.